Measurement of the Lambda(b) polarization and angular parameters in Lambda(b) -> J/psi Lambda decays from pp collisions at root s=7 and 8 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2018)
An analysis of the bottom baryon decay Lambda(b) -> J/psi(-> mu(+)mu(-))Lambda( -> p pi(-)) is performed to measure the Lambda(b) polarization and three angular parameters in data from pp collisions at root s = 7 and 8 TeV, collected by the CMS experiment at the Large Hadron Collider. The Lambda(b) polarization is measured to be 0.00 +/- 0.06(stat) +/- 0.06(syst) and the parity-violating asymmetry parameter is determined to be 0.14 +/- 0.14(stat) +/- 0.10(syst). The measurements are compared to various theoretical predictions, including those from perturbative quantum chromodynamics.
Keywords: WEAK DECAYS